1997
DOI: 10.1159/000461937
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration by Flow Cytometry of the Numbers of Residual White Blood Cells and Platelets in Filtered Red Blood Cell Concentrates and Plasma Preparations

Abstract: Background and objectives: New-generation polyester filters provide significant depletion of white blood cells (WBC) and platelets (PLT) in filtered red blood cell concentrates (FRCC) and in filtered plasma preparations (FP). The aim of this study was to elaborate a sensitive flow cytometric method for monitoring residual WBC and PLT in FRCC and FP. Materials and methods: We determined the number of WBC in 500 µl FRCC of FP using 50 µl of a combination of monoclonal antibodies (MAB) against CD45 (FITC labeled)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…The National Blood Service (NBS), England, has implemented universal leucocyte depletion of the blood supply as a precautionary measure against the possible risk of transmission of variant Creutzfeldt-Jacob disease (vCJD). To assess the performance of leucocyte-depletion systems, different methods, such as Nageotte [1], Imagn 2000 microvolume fluorimetry [2] and flow cytometry [3], have been developed to ensure accurate and precise counting of residual leucocytes in leucocyte-depleted products [4].…”
Section: Introductionmentioning
confidence: 99%
“…The National Blood Service (NBS), England, has implemented universal leucocyte depletion of the blood supply as a precautionary measure against the possible risk of transmission of variant Creutzfeldt-Jacob disease (vCJD). To assess the performance of leucocyte-depletion systems, different methods, such as Nageotte [1], Imagn 2000 microvolume fluorimetry [2] and flow cytometry [3], have been developed to ensure accurate and precise counting of residual leucocytes in leucocyte-depleted products [4].…”
Section: Introductionmentioning
confidence: 99%
“…Several reports in the literature have indicated that for low concentrations of WBCs in LR RBC and PLT products, counts determined by Nageotte hemocytometer and microscopy provided results with either comparable precision 16,30 or less favorable than those observed by automated methods such as microfluorometry or flow cytometry. 1,17,18 While the coefficients of variation determined by flow cytometry in the present study are similar to those reported in the literature, 7,15,19,31 those determined by the Nageotte method were smaller than previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…These values compare favorably to those reported in the literature. 7,14,[16][17][18][19]30,31,[35][36][37] Given that the pass or fail criteria for permitted rWBCs in RBC or apheresis PLT components in North America is less than 5 ¥ 10 6 per unit and less than 0.83 ¥ 10 6 per single-donor PLT in North America, the absolute WBC count per mL would fall in the range of approximately 15 Ϯ 3 WBCs per mL. The test sensitivity of 0.1 WBC per mL is approximately 1/150 of this value.…”
Section: Discussionmentioning
confidence: 99%
“…Since 1998, 11 developed countries have introduced routine leukocyte filtration with the aim of reducing some of these risks: Austria, Canada, France, Ireland (Eire), Germany, New Zealand, Norway, Portugal, United Arab Emirates, UK and the United States. Filtration with the most effective filters currently available results in approximately 4 log 10 reduction of the number of leukocytes [41]. It is uncertain whether, without further processing, residual leukocytes that are present in leukoreduced platelet concentrates might still present transfusion-associated risks to the recipient.…”
Section: Transfusion Of Residual Leukocytesmentioning
confidence: 99%